ANALISIS TINGKAT STRES PADA IBU RUMAH TANGGA DI KOTA YOGYAKARTA PASCA KENAIKAN HARGA BAHAN BAKAR MINYAK (BBM) - Cornelia Budimarwanti (Jurnal Penelitian Humaniora, 2008)
This Research is aimed to find out the opinions of housewives of low-middle economic classes towards the government’s policy in increasing the refined fuel oil’s price, to determine the impacts which are experienced by housewives both physically and physiologically after the increasing price of refined fuel oil (BBM) and to determine the stress level of which is experienced by housewives of low-middle economic classes after such increase. The samples were taken from housewives in Yogyakarta City of low-middle economic status. The total of the samples are 126 and taken from 9 sub-districts. This research employs 2 instruments, observation and questionnaire sheets. The housewives’ opinions to the policy of price increase of BBM are divided into three groups. They are the objecting housewives, no commenting-house wives and the housewives who think that such increasing price is a normal occurrence. The result of analysis shows that, in general, the stress level of housewives living in Yogyakarta after the increasing price of refined fuel oil (BBM) is included into very low category; in details of 46.8 % respondents with very low stress level, 35.7% respondents with low stress level, 15.1 % respondents with medium stress level and 2.4 respondents with high stress level.